Sistem Pendukung Keputusan Pemilihan Pemenang Lomba Masak Serba Ikan Tingkat Provinsi Dengan Menerapkan Metode Borda - Tami Juliandri Tambunan (KLIK: Kajian Ilmiah Informatika dan Komputer, 2021)
The cooking competition is an annual program of the Ministry of Marine Affairs and Fisheries, a fish cooking competition to introduce the diversity of dishes made from fish to the wider community. In selecting the winner of the cooking competition at the marine and fisheries service, it is still done manually without the role of a computerized system. Often there are mistakes in the selection of winners in cooking fish competitions, namely mistakes in calculations at the marine and fisheries service which are considered less effective and will cause misunderstandings in the future. Judging from these problems, a decision support system is needed. SPK is considered capable of providing solutions in selecting winners of cooking competitions at the marine and fisheries office. In the selection of the provincial level fish cooking competition, the marine and fisheries office uses the BORDA method which is considered capable of carrying out the best alternative selection and selection process so that it will get accurate results in the decisions taken and will assist the marine and fisheries service in selecting the winner of the fish cooking competition. provincial level